Correlation between sCD163 and clinicopathological severity in elderly patients with acute crescentic glomerulonephritis - Yuan Yi-meng; Zheng Qiao; Xie Ruo-lan; Hao Yan (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the correlation between soluble CD163 （sCD163） and clinicopathological severity in elderly patients with acute crescentic glomerulonephritis （CGN）.MethodsThirty-one elderly patients with CGN admitted to the Department of Nephrology of The First People's Hospital of Zigong City from March 2018 to March 2022 were selected as the study objects. Pathological classification was performed according to Berden classification， including the focal type， crescentic type， mixed type and sclerotic type. Among them， crescent type， mixed type and sclerotic type were classified as severe histopathological types. Serum and urine sCD163 levels were detected by enzyme-linked immunosorbent assay （ELISA）. Patients were followed up from diagnosis until they reached end-stage renal disease （ESRD） or death or the final follow-up date. ESRD was defined as requiring dialysis （hemodialysis or peritoneal dialysis）.ResultsUrinary sCD163 and serum sCD163 levels increased gradually with the increase in the clinicopathological severity， which remained highest in the sclerosing type［urinary 459.85 （416.288， 485.94） mg/g Cr， serum 249.60 （223.65， 401.13） μg/L］， followed by the mixed type ［urinary 338.29 （152.06， 357.01） mg/g Cr， serum 206.60 （166.18， 244.10） μg/L］ and crescentic type ［urinary 219.84 （158.96， 315.16） mg/g Cr， serum 137.75 （115.78， 206.43） μg/L］， and lowest in the focal type ［urinary 114.73 （82.95， 183.42） mg/g Cr， serum 98.30 （60.88， 125.35） μg/L］ （P<0.05）. The area under the curve （AUC） of urinary sCD163 before renal biopsy in distinguishing the focal type from the severe histopathological type was 0.848 （95%CI： 0.701-0.994）， with the corresponding cutoff value of 135.77 mg/gCr， specificity of 85.0%， and sensitivity of 81.8%. The AUC of serum sCD163 in distinguishing the focal type from the severe histopathological type was only 0.698 （95%CI： 0.504-0.892）. By Spearman analysis， urinary sCD163 level was positively correlated with serum sCD163 and creatinine， and negatively correlated with estimated glomerular filtration rate. Multivariate Logistic regression analysis showed that urinary sCD163 was an independent risk factor for severe histomatological types （P<0.05）. Kaplan-Meier curve analysis showed that the median ESRD-free survival time was 647 days in low-sCD163 patients and 253 days in high-sCD163 patients （Log Rank χ2=8.740， P=0.003）.ConclusionHigh levels of urinary sCD163 are associated with severe clinicopathological types in patients with CGN， and it is a promising parameter for predicting the severity of histopathological outcomes.